Characteristics Associated With Presence of Pediatric Mental Health Care Policies in Emergency Departments. Issue 12 (December 2021) - Cree, Robyn A.; So, Marvin; Franks, Jessica; Richards, Rachel; Leeb, Rebecca; Hashikawa, Andrew; Krug, Steven; Ludwig, Lorah; Olson, Lenora M.
Abstract : Objectives: The majority of US children do not have access to an emergency department (ED) with a pediatric mental health care policy in place. Our objective was to understand factors associated with whether US EDs have a pediatric mental health care policy. Methods: We analyzed data from the National Pediatric Readiness Project, a nationally representative cross-sectional survey of US EDs. Nurse managers reported whether their hospitals had a policy to care for children with social/mental health concerns (n = 3612). We calculated prevalence estimates, prevalence ratios (PRs), and confidence intervals (CIs) for regional and ED characteristics (eg, rurality and types of personnel) by whether EDs had a pediatric mental health care policy. Results: Overall, 46.2% (n = 1668/3612) of EDs had a pediatric mental health care policy. Emergency departments located in remote areas were 60% less likely to have such a policy compared with EDs in urban areas (PR, 0.4; CI, 0.3–0.5). Emergency department characteristics associated with having a pediatric mental health care policy included having a policy to transfer children with social/mental health concerns (PR, 5.4; CI, 4.7–6.2), having a policy to address maltreatment (PR, 3.4; CI, 2.6–4.4), and having nurse and physician pediatric emergency care coordinators (PR, 1.6; CI, 1.5–1.8). Conclusions: Lower prevalence of pediatric mental health policies in rural EDs is concerning considering EDs are often the first point of contact for pediatric patients. This work highlights the importance of pediatric emergency care coordinators in fostering ED capacity to meet children's mental health needs.